Bacteriological study of nasopharyngeal carriage of the child with nasopharyngitis - Baba, Sacko Hamidou; Mahamane, Maiga Ibrahim; Aminata, Kodio; Gadi, Timbine Lassina; Dicko, Abdoul Razak; Bourema, Kouriba; Dicko, Bagayogo Hawa (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Nasopharyngitis is a public health problem due to the high frequency of medical consultations involving this condition, the significant economic cost of drug prescriptions. The etiologies are diverse, its management, first medicinal (whose contribution of bacteriology among many others), may require for some palpating indications a surgical cure. The objective was to identify the main bacteria responsible for nasopharyngitis in children within the ENT department of the District Hospital CIV Bamako. Methods: This was a prospective cross-sectional study, over a period of 4 months, from 1 December 2018 to 31 March 2019 involving children with nasopharyngitis seen in consultation. The samples were taken by swabbing the nasopharynx using a sterile swab in accordance with the rules of asepsis and sterility and in the absence of antibiotic intake. Results: A total of 51 nasopharyngeal swabs were taken and analyzed using usual laboratory methods, 26 strains were isolated from 24 children. The age group of 1 to 4 years was mainly concerned. Main germs identified were Kocuria rosea 30.8%, Staphylococcus aureus 15.4%, Kocuria varians 11.5% Staphylococcus pneumoniae 7.7%. We observed a low percentage of resistance to penicillin G and tetracyclins. The majority of our strains were sensitive to macrolids. Conclusions: Nasopharyngitis of the child initial viral pathology, but whose clinical course may involve superinfection germs promoting complications. The bacteriological study of nasopharyngeal carriage rightly allows antibiotic therapy adapted to the germs in question, in this multivariate management of the nasopharyngeal disease of the child within our department.